2021
DOI: 10.1038/s41598-021-84624-9
|View full text |Cite|
|
Sign up to set email alerts
|

IL-23p19 and CD5 antigen-like form a possible novel heterodimeric cytokine and contribute to experimental autoimmune encephalomyelitis development

Abstract: Among various cytokines, interleukin (IL)-12 family cytokines have very unique characteristics in that they are composed of two distinct subunits and these subunits are shared with each other. IL-23, one of the IL-12 family cytokines, consists of p19 and p40 subunits, is mainly produced by antigen-presenting cells, and plays a critical role in the expansion and maintenance of pathogenic helper CD4+ T (Th)17 cells. Since we initially found that p19 is secreted in the culture supernatant of activated CD4+ T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Both CD4+ T-cell-specific conditional p19-deficient mice and complete CD5Ldeficient mice showed significantly alleviated EAE symptoms with a reduced frequency of GM-CSF + CD4+ T cells. All together, these studies reveal the p19/CD5L complex as a potential novel heterodimeric cytokine that contributes to EAE development [29].…”
Section: Iga Nephropathymentioning
confidence: 86%
See 2 more Smart Citations
“…Both CD4+ T-cell-specific conditional p19-deficient mice and complete CD5Ldeficient mice showed significantly alleviated EAE symptoms with a reduced frequency of GM-CSF + CD4+ T cells. All together, these studies reveal the p19/CD5L complex as a potential novel heterodimeric cytokine that contributes to EAE development [29].…”
Section: Iga Nephropathymentioning
confidence: 86%
“…Other studies also identified CD5L as a switch that regulates the functional state of helper CD4+ T (Th)17 cells and restrains their pathogenicity [28,29]. Th17 cells have diverse functions.…”
Section: Inflammatory Responses In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 Soluble p19, a subunit of IL-23, binds CD5L to form a p19/CD5L dimer that activates STAT5 to promote ThGM-CSF differentiation. 70 Of note, polymorphism in IL-2RA is one of the highest genetic risk factors for MS, as well as IL-7RA. 10 Polymorphisms in IL-2RA are associated with higher production of GM-CSF by memory T cells in healthy individuals, and with increased clinical severity in MS patients.…”
Section: Cd4 T Cellsmentioning
confidence: 99%
“…Последние, ингибируя экспрессию RORC, подавляют образование Th17-клеток, но под влиянием «провоспалительных» цитокинов могут трансформироваться в «патогенные» Th17-клетки -так называемый феномен «пластичности» Th17/Трег [12]. Выявлены дополнительные гены (Gpr65, Toso, Plzp), связанные с поддержанием «патогенности» Th17-клеток и CD5-антиген-подобный белок (CD5L, CD5 antigen-like), отменяющий патогенный потенциал Th17-клеток [13]. До недавнего времени предполагали, что Th17-клетки, индуцированные ТФР-β и ИЛ-6, обладают слабой «патогенностью» и не способны индуцировать аутоиммунную патологию.…”
Section: роль цитокинов оси ил-23/ил-17 в развитии иммуновоспалительн...unclassified